Medical students’ knowledge about human papillomavirus (HPV), HPV vaccine and head and neck cancer - Norangelys Solis-Torres; Isardo Braverman-Diaz; Luis A. Rivera-Morales; Jose J. Perez-Sanchez; Valeria S. Perez-Bravo; Angel J. Neris-Sanchez; Alexis Vera; Yaritza Diaz-Algorri (Human Vaccines & Immunotherapeutics)
The Human Papillomavirus (HPV) is a sexually transmitted infection that significantly affects the population worldwide. HPV preventive methods include vaccination, prophylactics, and education. Different types of cancers associated with HPV usually take years or decades to develop after infections, such as Head and Neck Cancer(HNC). Therefore, HPV prevention can be considered cancer prevention. A sample of medical students in Puerto Rico was evaluated to assess their knowledge about HPV, HPV vaccine, and HNC through two previously validated online questionnaires composed of 38 dichotomized questions, we measured HPV, HPV vaccination(HPVK), and HNC knowledge (HNCK). Out of 104 students surveyed, the mean HPVK score obtained was 20.07/26, SD = 3.86, while the mean score for HNCK was 6.37/12, SD = 1.78. Bidirectional stepwise regression showed study year and HPV Vaccine name had been the most influential variables on HPVK and HNCK. MS1 participants scored lower than MS2-MS4 participants, with no significant difference between MS2-MS4 scores. The results reveal knowledge gaps in HPV/HPV Vaccine and HNC among surveyed medical students. Our findings also suggest an association between knowledge of personal vaccination status, self-perceived risk, and how uncertainty in these factors may affect the medical students’ understanding of HPV, HPV vaccination, and associated cancers.